Diabetes and Clinical Outcome in Patients With Metastatic Colorectal Cancer: CALGB 80405 (Alliance). Issue 1 (17th October 2019) - Brown, Justin C; Zhang, Sui; Ou, Fang-Shu; Venook, Alan P; Niedzwiecki, Donna; Lenz, Heinz-Josef; Innocenti, Federico; O'Neil, Bert H; Shaw, James E; Polite, Blase N; Denlinger, Crystal S; Atkins, James N; et al.
Abstract: Background: Diabetes is a prognostic factor for some malignancies, but its association with outcome in patients with advanced or metastatic colorectal cancer (CRC) is less clear. Methods: This cohort study was nested within a randomized trial of first-line chemotherapy and bevacizumab and/or cetuximab for advanced or metastatic CRC. Patients were enrolled at 508 community and academic centers throughout the National Clinical Trials Network. The primary exposure was physician-documented diabetes at the time of enrollment. The primary endpoint was overall survival (OS); secondary endpoints were progression-free survival (PFS) and adverse events. Tests of statistical significance were two-sided. Results: Among 2326 patients, 378 (16.3%) had diabetes. The median follow-up time was 6.0 years. We observed 1973 OS events and 2173 PFS events. The median time to an OS event was 22.7 months among those with diabetes and 27.1 months among those without diabetes (HR = 1.27, 95% CI = 1.13 to 1.44; P < .001). The median time to a PFS event was 9.7 months among those with diabetes and 10.8 months among those without diabetes (HR = 1.16, 95% CI = 1.03 to 1.30; P = .02). Patients with diabetes were more likely to experience no less than grade 3 hypertension (8.1% vs 4.4%; P = .054) but were not more likely to experience other adverse events, including neuropathy. Conclusions: Diabetes is associated with an increased risk of mortality and tumor progression in patients with advanced or metastatic CRC. Patients with diabetes tolerate first-line treatment with chemotherapy and monoclonal antibodies similarly to patients without diabetes.